Acmeological Principles, Determinants and Technologies of Development of Ecological Awareness of the Future Experts - A V Gagarin; R A Turchaeva (Peoples' Friendship University of Russia (RUDN University), 2008)
The acmeological approach as a core basis of the development of ecological awareness of the future experts is considered in the article, and in this connection the acmeological principles, determinants and technologies of the specified process are disclosed.